The Effect of Health Education Through “ASENTIV” Leaflet Media on The Interest of Woman of Childbearing Age in Performing VIA Tests - Widyani, Bernadita; Wijayanti, Lumastari Ajeng; Titisari, Ira; Rahayu, Dwi Estuning; Marianthi, Dewi (Poltekkes Kemenkes Aceh, 2025)
Background: The incidence of cervical cancer in Indonesia has increased to 2 per 1,000 population. Low early detection rates are a major contributing factor to the rise in cervical cancer cases. This low coverage is influenced by low interest among women of childbearing age, related to a lack of knowledge, perceived health, and fear of the VIA test. The leaflet